Influence of Overlapping Tracks on Microstructure Evolution and Corrosion Behavior in Laser-melt Magnesium Alloy - Guan, Ying Chun (2016)
Overlapping of laser beam tracks has significant influence on surface quality of laser-treated materials. This paper examines how overlapping tracks affect heat flow, solidification microstructure and electrochemical behavior of laser-melt magnesium alloy. Microstructure evolution of laser-melt surface with different overlapping rates at optimized scanning speed is investigated. Results show that solidification microstructure changes from cellular grains to cellular–dendritic and equiaxed dendritic in the overlapped area when overlapping rate increases. Numerical model suggests that Marangoni convection plays a predominate role in determining the solidification microstructure, and it increases significantly with the overlapping rate. The effect of microstructure in-homogeneities caused by overlapping on electrochemical behavior has also been analyzed.